PENGARUH UKURAN PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO - Vivi Indriana; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the effect of company size and corporate governance on corporate risk disclosure. Independent variable in this study are company size (total asset, total sales, and number of company employees), concentrated ownership structure, independent board of directors, independent board of commissioners, educational background of the chief commissioner, independent audit committee, and type of auditor. Dependent variable used in this study is risk disclosure.This study used secondary data. The population in this study were 456 manufacturing companies’ annual report listed on the Indonesia Stock Exchange in 2014-2016. Based on the purposive sampling method, the samples obtained were 141 companies. The hypothesis in this study was tested using multiple regression analysis.The results of the analysis show that the variable total assets, total sales, number of employees, independent board of directors, auditor type have a positive relationships on risk disclosure. Concentrated ownership structures have a negative relationship on risk disclosure. Independent board of commissioners, educational background of the president commissioner, and independent audit committee have no relationship on risk disclosure.